Carbon sequestration associated to the land-use and land-cover changes in the forestry sector in Southern Brazil - Ronquim, Carlos C.; Silva, Ramon F. B.; Figueiredo, Eduardo B. de [UNESP]; Bordonal, Ricardo O.; Teixeira, Antonio H. de C.; Cochasrk, Thomas C. D.; Leivas, Janice F.; Neale, CMU; Maltese, A. (Spie-int Soc Optical Engineering, 2016)
We studied the Paraiba do Sul river watershed, Sao Paulo state (PSWSP), Southeastern Brazil, in order to assess the land use and cover (LULC) and their implications to the amount of carbon (C) stored in the forest cover between the years 1985 and 2015. The region covers an area of 1,395,975 ha. We used images made by the Operational Land Imager (OLI) sensor (OLI/Landsat-8) to produce mappings, and image segmentation techniques to produce vectors with homogeneous characteristics. The training samples and the samples used for classification and validation were collected from the segmented image. To quantify the C stocked in aboveground live biomass (AGLB), we used an indirect method and applied literature-based reference values. The recovery of 205,690 ha of a secondary Native Forest (NF) after 1985 sequestered 9.7 Tg (Teragram) of C. Considering the whole NF area (455,232 ha), the amount of C accumulated along the whole watershed was 35.5 Tg, and the whole Eucalyptus crop (EU) area (113,600 ha) sequestered 4.4 Tg of C. Thus, the total amount of C sequestered in the whole watershed (NF + EU) was 39.9 Tg of C or 145.6 Tg of CO2, and the NF areas were responsible for the largest C stock at the watershed (89%). Therefore, the increase of the NF cover contributes positively to the reduction of CO2 concentration in the atmosphere, and Reducing Emissions from Deforestation and Forest Degradation (REDD+) may become one of the most promising compensation mechanisms for the farmers who increased forest cover at their farms.
Keywords: Remote sensing; Forestry dynamics; Native forest; Eucalyptus; Paraiba do Sul River watershed